RESPON INTOLERANSI BERAGAMA BERDASARKAN 1 PETRUS 4: 12-14 - Marlon Butar-Butar (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
The issue of intolerance and violations of religious freedom in Indonesia threatens interfaith harmony, especially for Christian students. This study aims to analyze the biblical response to religious intolerance according to 1 Peter 4:12-14 and provide practical guidance for Christian students in facing persecution. The method used is qualitative, with a descriptive analysis of the biblical text. The results show that suffering and persecution are part of the Christian faith, where persecution is understood as a trial that strengthens faith. In conclusion, Christian students need to be equipped with an understanding of religious moderation, in-depth Christian education, and church training to wisely and compassionately face intolerance, enabling them to remain steadfast in faith while respecting the diversity around them.